2013
DOI: 10.1016/j.fsigen.2012.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Developmental validation of the PowerPlex® 18D System, a rapid STR multiplex for analysis of reference samples

Abstract: As short tandem repeat markers remain the foundation of human identification throughout the world, new STR multiplexes require rigorous testing to ensure the assays are sufficiently robust and reliable for genotyping purposes. The PowerPlex(®) 18D System was created for the direct amplification of buccal and blood samples from FTA(®) storage cards and reliably accommodates other sample materials. The PowerPlex(®) 18D System allows simultaneous amplification of the 13 CODIS loci and amelogenin along with four a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…However, most of these studies evaluated fresh blood samples which are applied immediately on the FTA cards, although other sample types also have been reported [11,[15][16][17]. Many of these studies have targeted forensically-relevant STR markers [18,19] or single nucleotide polymorphisms (SNPs) [20], and only few studies report the results from genome wide association studies [21]. DNA quality and quantity in PM samples with variable PM intervals (PMIs) stored on FTA paper have not tested to determine if such samples meet the demands of forensic or other genomic DNA analyses.…”
mentioning
confidence: 99%
“…However, most of these studies evaluated fresh blood samples which are applied immediately on the FTA cards, although other sample types also have been reported [11,[15][16][17]. Many of these studies have targeted forensically-relevant STR markers [18,19] or single nucleotide polymorphisms (SNPs) [20], and only few studies report the results from genome wide association studies [21]. DNA quality and quantity in PM samples with variable PM intervals (PMIs) stored on FTA paper have not tested to determine if such samples meet the demands of forensic or other genomic DNA analyses.…”
mentioning
confidence: 99%
“…In a typical forensic DNA laboratory, direct polymerase chain reaction (PCR) amplification is commonly employed to overcome these issues (Myers et al 2012;Tucker et al 2012). Direct amplification of STR loci reduces the time required for sample preparation and potentially helps laboratories to process increased number of samples (Wang et al 2011;Oostdik et al 2013;Hall and Roy 2014). In addition, the direct PCR amplification technique may also reduce risks of cross-over contamination (Caputo et al 2017;Ambers et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The document highlights key rules to follow by Forensic DNA laboratories in order to evaluate reliability, sensitivity, specificity, stability, and reproducibility of their methods. Unlike mRNA profiling, many validation experiments have been carried out on DNA marker based multiplex assay (Ensenberger et al, 2010;Oostdik et al, 2013;Oostdik et al, 2014). The authors have reported specifically validation of DNA multiplex kits with addition of more loci to the 13 core CODIS loci, enhanced buffer system with hot-start Taq DNA polymerase, sensitivity, concordance, inhibition tolerance amongst other criteria, following SWGDAM developmental validation guidelines; all these have made DNA typing more efficient and less time consuming.…”
Section: Introductionmentioning
confidence: 99%